The origins of “neurology” and “neurologist” - Andrew J Larner (Advances in Clinical Neuroscience & Rehabilitation)
Words define us, just as we define words.  Our clinical lives are permeated with our discipline of “neurology” (or other neuro-discipline) and our attribution as “neurologist” (or other neuro-profession).  Our professional organisations, such as the Association of British Neurologists, labels us as such.  But what are the origins of these words?  Whilst most neurologists will know that “neurology” originated with Thomas Willis in the 17th century, fewer will be familiar with the beginnings of “neurologist”.